The Development And Evaluation Of Water Irrigator For Plaque Removal - Azrul Hafiz Abdul Aziz; Nik Mohd Syahmi Zainuzzaman; Nur Aliah Afifah Ibrahim; Nadia Halib (International Islamic University Malaysia, 2024)
Non-Indexed Publication